"Angiodysplasia' of the tongue with acquired von Willebrand's disease. Issue 675 (January 1982) - Wood, G. M.; Losowsky, M. S.
Abstract : A case of acquired von Willebrand's disease is reported in which the patient developed a swelling on the dorsum of the tongue. Histology of this lesion closely resembled that described in angiodysplasia of the colon.